Pengaruh Model Pembelajaran Student Team Achievement Division (STAD) Terhadap Motivasi Belajar Pendidikan Agama Kristen Dan Budi Pekerti Siswa Kelas V Di SD Negeri 3 Pasar Pangururan Tahun Pembelajaran 2023/2024 - Ernina Nababan; Johari Manik; Tianggur Medi Napitupulu (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The research aims to determine the influence of the Student Team Achievement Division (STAD) learning model on the learning motivation for Christian Religious Education and Character Education of class V students at SD Negeri 3 Pasar Pangururan for the 2023/2024 Academic Year. The research hypothesis is that there is a positive influence between the Student Team Achievement Division (STAD) learning model on the learning motivation for Christian Religious Education and Characteristics of class V students at SD Negeri 3 Pasar Pangururan for the 2023/2024 academic year. Quantitative and descriptive research methods. The population of all class V students at SD Negeri 3 Pasar Pangururan for the 2023/2024 academic year who are Protestant Christians is 62 people. This research is population research. The research instrument is a closed number. The results of data analysis obtained: a) The value of rcount=0.561>rtable=0.254 shows that there is a positive influence between the Student Team Achievement Division (STAD) learning model and students' motivation to learn Christian Religious Education and Character. b) Regression equation. c) The determination test shows that the magnitude of the effect is 31.47%. d) Hypothesis testing obtained Fcount=26.756>Ftable=3.15 so H0 is rejected and Ha is accepted. The research concludes that there is a positive influence between the Student Team Achievement Division (STAD) learning model on the learning motivation for Christian Religious Education and Character Education of class V students at SD Negeri 3 Pasar Pangururan for the 2023/2024 Academic Year